Allopurinol-induced Agranulocytosis: A Case Report and Review - Aswanth Reddy; Arjun Sekar; Nkolika Nwankwo; Aswini Kumar (Brown Journal of Hospital Medicine, 2022)
Allopurinol, utilized in the treatment of gouty arthritis and hyperuricemia, is one of the most prescribed medications in general medical practice. Although well-tolerated, allopurinol can cause rare and severe adverse reactions, including bone marrow toxicity. A 68-year-old man presented to the hospital with severe neutropenia and aseptic meningitis. After an extensive workup, allopurinol was determined to be the culprit medication causing severe agranulocytosis, and his blood counts recovered upon discontinuing the drug. Drug-induced agranulocytosis is a rare but serious adverse reaction. Treatment includes supportive care and discontinuation of the offending agent.